The Potential of Pasak Bumi as a Food Supplement to Improve Spermatogenesis in Mice Model of Malnutrition - Ida Yuliana; Triawanti Triawanti; Didik Dwi Sanyoto; Husnul Khatimah; Asnawati Asnawati; Rayatul Aminah (Jurnal Berkala Kesehatan, 2021)
Malnutrition causes disruption of spermatogenesis in children. Pasak Bumi has the potential to increase spermatogenesis due to malnutrition. Aimed of research is to proved Pasak Bumi as a food supplement to improve spermatogenesis disorders due to malnutrition in malnourished rats. The research method used analytical observational method by observing the histological preparations of the testes of malnourished rats. Observations using a binocular microscope were analyzed with Optilab Camera and Image Raster software. There are 5 groups of experimental: M: malnutrition without intervention; P1: malnutrition + standard feed + PB 7.5 mg/kgBW; P2: malnutrition + standard feed + PB 15 mg/kgBW; P3: malnutrition + standard feed + PB 22.5 mg/kgBW; P4: malnutrition + standard feed + PB 30 mg/kgBW; Research parameters were number of seminiferous tubules, primary spermatocytes and Leydig cells. Data analysis used the Anova One way test with a confidence level of 95%. The results showed number of seminiferous tubules, primary spermatocytes and Leydig cells in the M group was less than the P1-P4 group. This suggests malnutrition causes disruption of spermatogenesis. Conclusion the administration of Pasak Bumi extract at various doses increased spermatogenesis in malnourished.